Institutionalizing Inequity: Ableism, Racism and IDEA 2004 - Beratan, Gregg D. (Disability Studies Quarterly, 2006)
For thirty years, the Individuals with Disabilities Education Act (IDEA) has been regarded as a civil rights legislation intended to fight discrimination against individuals with disabilities. While the sincerity of this claim is not in question, I contend that ableism is deeply ingrained within IDEA. Covert forms of discrimination, such as institutional ableism and racism, are far more insidious than overt discrimination because they are so difficult to question–as is the case with the Individuals with Disabilities Education Improvement Act of 2004 [IDEA 2004]. Using some of the techniques developed by scholars of both disability studies and critical race theory, I detail how IDEA 2004 embeds unintentional discrimination within the policies, structures and practices of the educational system. I argue that the institutions themselves (policies, practices, schools) become instruments of discrimination despite their stated purpose to end discrimination.